2007
DOI: 10.1093/toxsci/kfm178
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Plays a Major Role in the Maturation of Human Dendritic Cells Induced by NiSO4 but not by DNCB

Abstract: Dendritic cell (DC) activation is a critical event for the induction of an immune response to haptens. Although signaling pathways such as mitogen-activated protein kinase (MAPK) family members have been reported to play a role in DC activation by haptens, little is known about the implication of the nuclear factor kappa B (NF-kappaB) pathway. In this work, we showed that NiSO(4) induced the expression of HLA-DR, CD83, CD86, and CD40 and the production of interleukin (IL)-8, IL-6, and IL-12p40 in human DCs, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 37 publications
9
72
1
Order By: Relevance
“…The amounts of Ni and MALP-2 used in the current study were chosen on the basis of previous concentration-response analyses that indicate 200 mM NiSO 4 and 600 pg/ml MALP-2 are effective at achieving a synergistic induction of IL-6 in HLF (7). These concentrations are also within the range of what others have used in vitro with regard to IL-6 and CXCL8 release in response to MALP-2 (18) or NiSO 4 alone (19). After treatment, total RNA was extracted from the cells and cDNA was generated from 1 mg total RNA using Omniscript reverse transcriptase with oligo d(T) as a primer.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The amounts of Ni and MALP-2 used in the current study were chosen on the basis of previous concentration-response analyses that indicate 200 mM NiSO 4 and 600 pg/ml MALP-2 are effective at achieving a synergistic induction of IL-6 in HLF (7). These concentrations are also within the range of what others have used in vitro with regard to IL-6 and CXCL8 release in response to MALP-2 (18) or NiSO 4 alone (19). After treatment, total RNA was extracted from the cells and cDNA was generated from 1 mg total RNA using Omniscript reverse transcriptase with oligo d(T) as a primer.…”
mentioning
confidence: 67%
“…It has yet to be determined whether Ni and MALP-2 synergistically induce COX-2 mRNA through transcriptional or post-transcriptional mechanisms. Given that NFkB and C/EBP are important signaling pathways in inflammatory responses (37,38), and both MALP-2 and NiSO 4 can activate NFkB (19,39), one possible explanation is that Ni and MALP-2 activate C/EBP in concert with members of the NF-kB/Rel family to induce COX-2 promoter activity. Alternatively, it is also possible that the dramatic increase in COX-2 may be mediated, in part, through enhanced stabilization of COX-2 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…We and other authors showed that contact sensitisers activate the mitogen-activated protein kinases (MAPKs), mainly the p38 MAPK (Matos et al, 2005a,b;Koeper et al, 2007;Trompezinski et al, 2008). Moreover, we and other authors have shown that further downstream signals elicited by skin sensitisers include the activation of the transcription factors nuclear factor kappa-B (NF-kB) and activating protein-1 (AP-1) (Cruz et al, 2002Ade et al, 2007;Antonios et al, 2009). The following question remains: whether all contact sensitisers use the same signal transduction pathways as the stimuli known to induce DC maturation, such as lipopolysaccharide, proinflammatory cytokines, or CD40 ligand, or whether there is an innate cellular signalling pathway profile activated only by skin sensitisers.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of NF-κB to skin sensitization has recently been shown, again in nickel allergy. Ade et al (2007) showed that changes in the expression of activation-associated phenotypic markers were dependent upon NF-κB activation in DC exposed to NiSO 4 , but not in DC exposed to DNCB. This study not only provides evidence that NF-κB is important for the acquisition of sensitization to at least some contact allergens, but also supports evidence described above that indicates that nickel activates DC via interaction with the TLR4 pathway.…”
Section: Toll Like Receptorsmentioning
confidence: 96%
“…These genes code for a variety of proteins including phase II detoxifying enzymes and the pro-inflammatory chemokine IL-8. Importantly, it has been shown that many contact allergens interact with the Nrf2-Keap1-ARE toxicity pathway (Natsch et al, 2008;Ade et al, 2007). The view is, therefore, that interaction of contact allergens with the Nrf2-Keap1-ARE pathway may be an important component of signaling and inflammation in skin sensitization.…”
Section: Nrf2-keap1-are Toxicity Pathwaymentioning
confidence: 99%